Effect of synthesis methods and comparative study of structural properties of micro and nano Ferrites - Pathan, A. T.; Shaikh, A. M.; Sushant, S.K.; Mathad, Shridhar N. (Physics and Chemistry of Solid State, 2023)
In this study, Mn(x)Zn(1-x)Fe2O4 ferrite samples with x=0.4 and 0.6 were synthesized using a solid-state method and co-precipitation method. In order to determine the effects of various concentrations (x) on the ferrite's structure, particle size, and crystalline phases, prepared samples were analysed using X-ray diffraction (XRD). The XRD patterns revealed that the synthesized samples display a single-phase cubic spinel structure.FTIR analysis showed for both synthesis method have absorption band in the range 400 to 1000 cm-1.SEM analysis shows extreme homogeneity of all the samples. EDX analysis was used to examine for Mn0.4Zn0.6Fe204,The prepared ferrites powders contain Mn, Zn, and Fe, as shown in both synthesis methods.In this approach, alternative synthesis routes for these ferrites are suggested in this study in order to get around some limitations of the traditional preparation method.